Dialogue summary: Supporting rapid learning and improvement for select conditions in Canada - Moat, KA; Bhuiya, AR; Voorheis, P (My University, 2020)
A thematic summary of what was learned from the stakeholder dialogue on supporting rapid learning and improvement for select conditions in Canada, about the problem (and its causes), elements of a potentially comprehensive approach for addressing it, key implementation considerations, and possible next steps.
Keywords: rapid learning; improvement; conditions; Canada